Efektivitas Promosi Media Sosial Dalam Meningkatkan Brand Awareness Pada Generasi Milenial (Studi Pada Pasar Nou, Kota Gunungsitoli) - Lase, Siska Putri Cindian; Waruwu, Vinca Elvianty; Zebua, Yuendra; Zebua, Yuandra (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
The development of digital technology has changed the way businesses promote their products and services, including traditional markets. Social media is an effective marketing tool in reaching consumers, especially the millennial generation who are active in using digital platforms. This research aims to analyze the effectiveness of promotions via social media in increasing brand awareness of traditional markets, with a case study at Pasar Nou, Gunungsitoli City. The research method used is qualitative with data collection techniques through interviews, observation and documentation. The research results show that the use of social media as a promotional tool at Pasar Nou is still not optimal. Even though there is an increase in brand awareness among the millennial generation, factors such as traders' limited understanding of digital marketing, lack of consistency in content creation, and minimal interaction with the audience are the main obstacles to promotional effectiveness. This research concludes that social media has great potential in increasing brand awareness in traditional markets, but more targeted marketing strategies and education for traders are needed so that its use is maximized. The recommendations from this research are to increase digital marketing training for traders and optimize the use of interesting and interactive content to attract the attention of the millennial generation.